Are people better employees than machines? Dehumanizing language and employee performance appraisals. (22nd August 2021) - Fowler, Luke; Utych, Stephen
Abstract: Objective: Although performance appraisals are based on objective procedures, cognitive biases from appraisers may create avenues for errors in judgment of employee performance. Dehumanizing language, or metaphors that characterize humans in nonhuman terms (e.g., cogs in a machine), is one important way cognitive biases can occur Method: We conduct a survey experiment to determine if dehumanizing language affects perceptions of employee value or competency within the context of performance appraisals. Result: Findings show that when employees are referred to in mechanistic terms, respondents perceive that employee to be deserve hire compensation, and be more competent, as compared to referring to employees in human or animalistic terms. Conclusion: Conclusions suggest dehumanizing language is an important type of cognitive bias that affects individuals in administrative environments, and the managerial and ethical implications of its use require further examination.